Institutional Voids, Capital Markets and Temporary Migration : Evidence from Bangladesh - Bossavie, Laurent (World Bank, Washington, DC, 2022)
Limited access to credit due to poorly functioning institutions is a key constraint to business creation. This paper examines the role played by temporary migration in addressing the institutional void of limited access to loans by aspiring entrepreneurs. Using rich data from one of the major migrant-sending countries globally, Bangladesh, it provides evidence on how migration is employed as a common intermediate step to accumulate the capital required for entrepreneurship. The paper offers, for the first time, a detailed account of the financial costs and returns to temporary migration as a risky investment. It shows that international migration shares many common features with classical entrepreneurial investments: it requires the payment of a considerable upfront cost, generates high returns, and is risky. The paper shows that temporary migrants usually get high returns from their migration episode and are often successful in starting entrepreneurial activities back home, thanks to faster accumulation of savings overseas. Given the similarities shared by Bangladesh and other major migrant-sending countries globally, the key findings of the paper are relevant beyond the Bangladeshi context studied by this paper.